Prolonged Gastric Transit Time in Small-Bowel Capsule Endoscopy: Which Patients Are at Risk and What Are the Implications? - Freitas, Marta; Silva, Vítor Macedo; Xavier, Sofia; Carvalho, Pedro Boal; Rosa, Bruno; Moreira, Maria João; Cotter, José (Turkish Journal of Gastroenterology, 2023)
Background: Prolonged gastric transit time is a commonly described cause for incomplete capsule endoscopy examination. This study aimed to evaluate the prevalence and identify risk factors for prolonged gastric transit time and to assess its impact on the rate of incomplete examinations. Methods: This is a retrospective study including patients undergoing small-bowel capsule endoscopy between January 2014 and August 2020. Patients with prolonged gastric transit time were consecutively included and patients without prolonged gastric transit time were randomized (controls) in a 1:2 ratio. Prolonged gastric transit time was defined as small-bowel capsule endoscopy remaining in the stomach for more than 1 hour, as checked with the routine use of the real-time viewer, requiring an intervention such as prokinetic administration and/or endoscopically assisted capsule delivery into the duodenum. Results: Prolonged gastric transit time occurred in 45/957 patients (prevalence 4.7%). Both groups were similar regarding small-bowel capsule endoscopy indication and inpatient status. The mean small-bowel transit was similar between groups (4 hours 48 minutes ± 2 hours 11 minutes vs. 4 hours 38 minutes ± 1 hour 36 minutes; P =.74). Prolonged gastric transit time group did not have a significant higher rate of incomplete exams (P =.44) but presented more frequently with inadequate small-bowel preparation (P <.001). Older age (P =.046), female sex (P =.004), diabetes (P =.03), and psychotropic medication use (P =.02) were risk factors for prolonged gastric transit time. In multivariate analysis, female sex (odds ratio: 4.0; P =.002) and psychotropic medication use (OR: 4.6; P =.003) were predictors of prolonged gastric transit time. Conclusion: Prolonged gastric transit time was not associated with a higher rate of incomplete exams in our cohort but was associated with higher rate of inadequate small-bowel preparation. Female sex and psychotropic medication use were independent risk factors for prolonged gastric transit time. Cite this article as: Freitas M, Macedo Silva V, Xavier S, et al. Prolonged gastric transit time in small-bowel capsule endoscopy: Which patients are at risk and what implications? Turk J Gastroenterol. 2023;34(3):227-233.